HUBUNGAN TINGKAT SPIRITUAL DENGAN KUALITAS HIDUP ORANG DENGAN HIV/AIDS (ODHA) DI YAYASAN ANGEL HEART KOTA BATAM TAHUN 2018 - Fitta Deskawaty; Bratasena . (Universitas Batam, 2019)
People's perception of HIV / AIDS is transmitted through sexual relations that are considered immoral and embarrassing tends to discriminate against PLWHA. This negative stigma can indirectly reduce the quality of life of PLWHA. The low quality of life of PLWHA can affect their health. But in the end, all sufferers accept their condition as sufferers of HIV / AIDS by returning the problem to God. The spiritual role is very important in the process of acceptance because it has a positive influence marked by a reduction in depression, an improvement in the quality of life, a reduction in the fear of facing death, and a growing spirit of survival. This research method was observational analytic with a cross-sectional approach which was conducted at the Angel Heart Foundation in Batam City in 2018. The population in this study was people with HIV / AIDS at the Angel Heart Foundation in Batam City in 2018, amounting to 50 people, using retrieval techniques total sampling. The statistical test used was the chi-square test using a 95% significance level. 50 respondents, of which 30 respondents with a less spiritual level with a classification of 27 respondents (90.0%) had poor quality of life, and 3 respondents (10.0%) had a good quality of life. Meanwhile, 20 respondents with a good spiritual level with a classification of 1 respondent (5.0%) had poor quality of life and 19 respondents (95.0%) had a good quality of life. Statistical test results with chi-square obtained p-value = 0.00 <0.05, then Ho is rejected and Ha is accepted. There is a relationship between Spiritual Level and Quality of Life of People with HIV / AIDS (PLWHA) at Angel Heart Foundation Batam City in 2018.